Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Pasien Pengguna Bpjs Rawat Jalan Melalui Reputasi Rsud Regional La Mappapenning Kabupaten Bone - Ramadani, Reski; Razak, Mashur; Razak, Novita (STIM-LPI Makassar, 2026)
The purpose of this study is to (1) analyze the effect of service quality on outpatient satisfaction at La Mapapenning Regional Hospital Bone Regency (2) analyze the effect of trust on outpatient satisfaction at La Mapapenning Regional Hospital Bone Regency (3) analyze the effect of service quality on the reputation of La Mapapenning Regional Hospital Bone Regency (4) analyze the effect of trust on the reputation of La Mapapenning Regional Hospital Bone Regency (5) analyze the effect of BPJS outpatient satisfaction on the reputation of La Mappenning Regional Hospital, Bone Regency (6) analyze the effect of service quality on outpatient satisfaction through the reputation of La Mapapenning Regional Hospital Bone Regency (7) analyze the effect of trust on outpatient satisfaction through the reputation of La Mapapenning Regional Hospital Bone Regency. The population in this study were all outpatients at La Mappapenning Regional Hospital with a sample of 150 respondents based on the results of the Slovin formula. The analysis method used in this study uses smart PLS testing, descriptive analysis, and hypothesis testing. The results of this study indicate that (1) Service quality has a positive and significant effect on patient satisfaction (2) Trust has a positive and significant effect on patient satisfaction (3) Service quality has a positive and significant effect on hospital reputation (4) Trust has a positive and significant effect on hospital reputation (5) Patient satisfaction has a positive and significant effect on hospital reputation (6) Service quality has a positive and significant effect on patient satisfaction through hospital reputation (7) Trust has a positive and significant effect on patient satisfaction through hospital reputation.